Pegaruh Audit Internal dan Pengendalian Internal terhadap Pencegahan Kecurangan (Fraud) (Studi Empiris Pada PT Krakatau Steel) - Ahmad Ramzy Falah (Pascasarjana Universitas Sultan Ageng Tirtayas, 2022)
This study aims to examine the effect of internal audit, internal control on fraud (Fraud). This research is a type of quantitative research, data is collected from distributing questionnaires at PT KrakatauSteel. The formulation of the problem is whether Internal Audit has a significant effect on FraudPrevention? Does Internal Control have a significant effect on Fraud Prevention? Do Internal Auditand Internal Control simultaneously have a significant effect on Fraud Prevention? With data analysistechniques using multiple linear regression. The result of this study is that internal audit has no significant effect on fraud prevention. Internal control has a significant effect on fraud prevention